Bempedoic acid - new agent in hiperlipidemia treatment - literature review - Agata Frańczuk; Aleksandra Makłowicz; Jakub Plizga; Agnieszka Głuszczyk; Ewelina Kopczyńska; Angelika Szpulak; Michalina Grzelka; Katarzyna Kuleta; Katarzyna Słychan; Julia Głoskowska (Nicolaus Copernicus University in Toruń, 2024)
Hyperlipidemia is becoming more and more severe condition among modern society. High-fat diet, sedentary lifestyle, lack of physical activity are the common factors leading to overweight, obesity and problems with serum lipid control. Dyslipidemia is one of the most important agents contributing to cardiovascular diseases snd therefore lower quality of life, disability and preamature death. This forces to constatnt searching for lipid-lowering drugs, that can be successfully use in the patients suffering from poor lipid control. Bempedoic acid (ETC-1020) is one of the newest, first in the class medicine, firstly approved to use in the USA on 21st February 2020 in monotheraphy, and then on  26th February in combination with ezetimibe. It is a small synthetic prodrug molecule that is activated by acyl-CoA synthetase in the liver. Bempedoic acid inhibits competitively adenosine triphosphate citrate lyase (ACL) and as a result it stops the further production of cholesterol and fatty acids. Research shows the ability of ETC-1020 to decline of LDL-C cholesterol up to 24%. It is also responsible for total cholesterol, non-HDL-C, ApoB and hs-CRP reduction. Bempedoic acid is characterized by good pharmacokinetics and pharmacodynamics. ECT-1020 has also a good drug-to-drug interaction profile. Many clinical trials have reported efficacy and safety of use with minimal side effects. Because of its target point is located in the liver and kidney, it can be successfully use in patients with statin intolerance due to bypassing decline of muscle cholesterol biosyntheisis, that is the main cause of musculosketelar adverse effects.